2012
DOI: 10.1007/s10822-011-9523-0
|View full text |Cite
|
Sign up to set email alerts
|

Computational fragment-based screening using RosettaLigand: the SAMPL3 challenge

Abstract: SAMPL3 fragment based virtual screening challenge provides a valuable opportunity for researchers to test their programs, methods and screening protocols in a blind testing environment. We participated in SAMPL3 challenge and evaluated our virtual fragment screening protocol, which involves RosettaLigand as the core component by screening a 500 fragments Maybridge library against bovine pancreatic trypsin. Our study reaffirmed that the real test for any virtual screening approach would be in a blind testing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Our study found that results from RosettaLigand [147][148][149] display a similar performance for fragment like ligands as for druglike ligands. The chances of success in a fragment screening process could be increased significantly with careful selection of receptor structures, protein flexibility, sufficient conformational sampling within binding pocket and accurate assignment of ligand and protein partial charges [150]. There are number of studies reported in literature that identified potent fragment molecules utilizing structure based docking followed by experimental validation [140,[151][152][153].…”
Section: Screening Of Fragment Libraries By Computational Methodsmentioning
confidence: 99%
“…Our study found that results from RosettaLigand [147][148][149] display a similar performance for fragment like ligands as for druglike ligands. The chances of success in a fragment screening process could be increased significantly with careful selection of receptor structures, protein flexibility, sufficient conformational sampling within binding pocket and accurate assignment of ligand and protein partial charges [150]. There are number of studies reported in literature that identified potent fragment molecules utilizing structure based docking followed by experimental validation [140,[151][152][153].…”
Section: Screening Of Fragment Libraries By Computational Methodsmentioning
confidence: 99%
“…Kumar and Zhang evaluated their VS protocol with RosettaLigand by screening a 500-fragment Maybridge library. [106] They highlighted the importance of an appropriate method for the calculation of partial charges. They also confirmed that using multiple receptor ensembles in docking does not always yield better enrichment than individual receptors, a finding previously observed in other studies.…”
Section: Fragment Dockingmentioning
confidence: 99%
“…Affinity prediction results in some cases were reasonable, however[49]. The SAMPL3 protein-ligand challenge involved predicting binding of a series of fragments to trypsin [39], and a number of groups participated[30, 50, 31, 49, 2], in some cases achieving rather good enrichment for screening [50, 49] and good correlations between predicted binding strength and measured affinity[50], though the test was still challenging[31]. …”
Section: Introductionmentioning
confidence: 99%